Analysis Of Derivational Affixes Found In Sentences Written By The Efl Students Of Tadulako University - Shanti Rachmawati Afrilya; Siska Bochari; Hastini; Mochtar Marhum (Universitas Cokroaminoto Palopo, 2024)
The objectives of this study were to find out the most dominant and the most difficult function of derivational affixes in the sentences written by the students, and also to know the factor that influences students difficult to use the function of derivational affixes. The design of this study was quantitative descriptive with population were the 5th semester students of English education study program of Tadulako University who have taken the Morphology subject. The sample of this study was 151 students of the 5th semester students used simple random sampling technique. The instruments to collect the data were test and questionnaire. The result of the data analysis show that: (1) the most dominant function of derivational affixes used by the students was verbal suffix –ize that has function to change noun become verb, (2) the most difficult function of derivational affixes used by the students was the suffix -wise as the adverbial suffix that attached to a noun to form an adverb, (3) there were two factors influencing the students difficult in using the function of derivational affixes which was internal factor.